SCIENTIFIC AND METHODOLOGICAL BASES OF FORMING HEALTH-RELATED SKILLS IN FUTURE EDUCATORS - Dadajonova Zarnigor Foziljon kizi (Bright Mind Publishing, 2025)
This article analyzes the scientific and theoretical foundations of developing health-related skills among future preschool educators, as well as the existing challenges and possible solutions. It is scientifically substantiated that the process of forming healthy lifestyle habits in preschool children is closely connected with the educator’s professional competence, psychological culture, and ability to create a healthy environment. Based on the competency-based, activity-oriented, and integrative approaches, a methodological model was proposed. The results of the study have practical significance for improving the quality of preschool education, promoting a healthy educational environment, and enhancing the health-related preparedness of future educators.
Keywords: Future educator, health competence, preschool education, healthy lifestyle, methodological model, competency-based approach.